Nursing of a patient with post-stroke constipation treated by acupoint massage along meridians (循经穴位按摩治疗脑卒中后便秘1例的护理体会) - GENG Liqiu (耿力秋); LIU Guiying (刘桂英) (中西医结合护理)
This paper summarized the nursing measures for a patient with post-stroke constipation treated by acupoint massage along meridians. Based on a comprehensive nursing risk assessment, the acupoint massage manipulations along meridians was carried out in combination with psychological care and dietary guidance. The acupoint massage was effective to relieve the symptoms of constipation. (本文总结运用循经穴位按摩治疗1例脑卒中后便秘患者的效果和护理体会。在完善护理评估的基础上, 运用循经穴位按摩手法, 同时配合心理护理和饮食指导, 有效改善患者便秘症状。)